Development and characterization of functionalized Al2O3 and TiO2-reinforced polybenzoxazine nanocomposites. Issue 1 (2nd January 2016) - Lakshmikandhan, T.; Chandramohan, A.; Sethuraman, K.; Alagar, M.
Abstract: In the present work, benzoxazine was synthesized using caprolactam amine and cardanol, and its molecular structure was confirmed with FTIR and NMR spectroscopic techniques. Alumina (Al2 O3 ) and titania (TiO2 ) were functionalized using 3-aminopropyltrimethoxysilane (APTMS). The nanocomposites were developed by reinforcing with varying weight (1, 3, 5, and 7) percentages of functionalized Al2 O3 (F-Al2 O3 ) and functionalized TiO2 (F-TiO2 ) with benzoxazine. The developed nanocomposites (F-Al2 O3 /CPBz and F-TiO2 /CPBz) were characterized from their thermal, dielectric, and UV shielding studies. Data obtained from thermal studies show that 7 wt% of F-Al2 O3 -reinforced cardanol-based polybenzoxazine nanocomposite exhibits higher thermal stability than that of 7 wt% F-TiO2 -reinforced cardanol-based polybenzoxazine nanocomposite. Dielectric and UV shielding studies show that 7 wt% F-TiO2 nanocomposite show higher value of dielectric constant (10.2) and UV shielding value (93%) than those of neat and other weight percentages of F-Al2 O3 and F-TiO2 reinforced composites.